2022
DOI: 10.1371/journal.pone.0263980
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic MYC insertions in Burkitt lymphoma: New data and a review of the literature

Abstract: The occurrence of MYC-negative Burkitt lymphoma (BL) has been discussed for many years. The real frequency of the MYC insertion in MYC-negative BL is still unknown. Fine-needle aspiration biopsies of 108 consecutive patients with clinicopathologically suspected BL (suspBL) were evaluated by flow cytometry, classical cytogenetics, and fluorescence in situ hybridization (FISH). We found 12 cases (11%) without the MYC rearrangement by FISH with a MYC breakapart probe: two patients (1.9%) with cryptic MYC/IGH fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…In MCL, concurrent TP53 and CDKN2A gene aberrations correlate with chemoresistance [50]. In BL, we already assessed the prognostic role of MYC insertions or concomitant BCL2 and BCL6 mutations [46, 51]. In B-ALL/LBL and HGBL with MYC and BCL2 and/or BCL6 rearrangements, NGS sequencing has shown recurrent variants of genes coding for transcription factors (MYC, FOXO1), epigenetic modulators (KMT2D, EZH2, and CREBBP), and antiapoptotic proteins (BCL2) [51, 52].…”
Section: Ancillary Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In MCL, concurrent TP53 and CDKN2A gene aberrations correlate with chemoresistance [50]. In BL, we already assessed the prognostic role of MYC insertions or concomitant BCL2 and BCL6 mutations [46, 51]. In B-ALL/LBL and HGBL with MYC and BCL2 and/or BCL6 rearrangements, NGS sequencing has shown recurrent variants of genes coding for transcription factors (MYC, FOXO1), epigenetic modulators (KMT2D, EZH2, and CREBBP), and antiapoptotic proteins (BCL2) [51, 52].…”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…Molecular testing for LN-FNAC was traditionally limited to IGH/TCR receptor assessment for clonality testing [44,45]. Nonetheless, different studies have assessed that LN-FNAC samples are suitable for extensive and accurate analysis [13,39,40,[46][47][48][49].…”
Section: Molecular Testingmentioning
confidence: 99%
“…Therefore, establishing a MYC status in these patients is essential for prognostic purposes. Due to cryptic rearrangements and variation in MYC breakpoints, both chromosome and fluorescence in situ hybridization (FISH) analysis may fail to detect these translocations in some cases [ 15 , 16 , 17 ]. In case of FISH analysis, up to 10% of the cases may be incorrectly identified [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, 8q24 breakpoints were mapped greater than 350-645 kb 3′-downstream from MYC inside a cluster region [22]. Consequently, current commercially available FISH probes such as the dual color dual fusion probe set and the MYC break-apart probe may both fail to detect MYC R. Furthermore, other genetic alterations such as mutations, cryptic insertion of MYC into IGH, cryptic insertion of IG regulatory regions into MYC, deregulation of micro RNA-34B, or single nucleotide polymorphisms at 8q24 that may convey a shared underlying biology to MYC R have been implicated [15]. In fact, Hilton et al [23] showed that the expression signature of MYC high grade DLBCL in which MYC had either cryptic alterations or rearrangements with non-IG partners is similar to the MYC double-hit DLBCL.…”
mentioning
confidence: 99%
“… 3 Therefore, patients with leukemia with BL morphology and no MYC rearrangement may be diagnosed as BL-like ALL, BL without MYC rearrangement, or BL with cryptic MYC rearrangement, on the basis of next-generation sequencing. 4 However, distinctions should be made because of differences in management and prognosis.…”
Section: Introductionmentioning
confidence: 99%